The Strategic Role of the Indonesian Language in Leadership and Corporate Management - Mohzana, Mohzana; Al-Pansori, Muh. Jaelani; Rismawati, Lia (Sumber Belajar Sejahtera, 2025)
This articel explores the role of the Indonesian language in leadership communication within corporate organization management. Given Indonesia’s linguistic and cultural diversity, the Indonesian language serves as an essential communication tool for fostering harmonious relationships among organizational members. This study examines how the proper and effective use of Indonesian can enhance communication effectiveness, strengthen organizational identity, and promote better collaboration. Through an in-depth literature review, this journal highlights the importance of appropriate word choice and grammar in organizational communication and their impact on performance and professionalism. The findings indicate that proficiency in language not only reflects individual character but also significantly contributes to an organization’s overall success.